IMPLEMENTATION OF THE MEDIATION PROCEDURE IN RESOLVING CONFLICT SITUATIONS IN OCCUPATIONAL PATHOLOGY IN ORDER TO INCREASE THE EFFICIENCY OF DISPUTE RESOLUTION - Ксения Валерьевна Гаврылышена; Виктор Андреевич Семенихин; Сергей Николаевич Филимонов; Елена Владимировна Часовских (Медицина в Кузбассе, 2022)
The high prevalence of occupational diseases among workers employed in the coal mining industry causes the problem of renting employees to establish an occupational disease, and in case of refusal due to the disease with the profession, the number of applications to the judiciary increases.